2004
DOI: 10.1159/000080310
|View full text |Cite
|
Sign up to set email alerts
|

Carditis at the Interface between GERD and <i>Helicobacter pylori</i> Infection

Abstract: Inflammation of the gastric cardia (‘carditis’) is a histological diagnosis. It seems reasonable to transfer histological criteria of the updated Sydney classification from the distal stomach to the cardia as long as a special classification of inflammation of the esophagogastric junction is lacking. The two best characterized causes of carditis are Helicobacter pylori infection and gastroesophageal reflux disease (GERD). However, the causal contribution and interference of these two factors are highly controv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…H. pylori colonisation in the oesophageal mucosa, which correlated with inflammatory changes, was also reported 170. However, inflammation in the cardia occurs even without H. pylori infection and has been shown to be associated with GOR 44 79 169 171–173. Chronic inflammation of the GOJ mucosa appears to be the immediate consequence of GORD, correlating with endoscopic diagnosis,169 and occurs without H. pylori infection 44 79 169 171…”
Section: Resultsmentioning
confidence: 83%
“…H. pylori colonisation in the oesophageal mucosa, which correlated with inflammatory changes, was also reported 170. However, inflammation in the cardia occurs even without H. pylori infection and has been shown to be associated with GOR 44 79 169 171–173. Chronic inflammation of the GOJ mucosa appears to be the immediate consequence of GORD, correlating with endoscopic diagnosis,169 and occurs without H. pylori infection 44 79 169 171…”
Section: Resultsmentioning
confidence: 83%
“…Because the length of the CM increases with age, some investigators believe the CM to be metaplastic 26 . It remains unknown as to: (i) the relationship between the length of CG, the CM, and developmental age; (ii) the status of superficial esophageal CG as a normal developmental structure; and (iii) whether or not there are the differences in the CG and the CM among different ethnic populations.…”
Section: Pediatric Populationmentioning
confidence: 99%
“…The expression of these different glycoproteins results in distinct lectin-binding capabilities [6,7,8]. Both abnormal gastroesophageal reflux and H. pylori lead to inflammation and, in a subset of patients, to intestinal metaplasia at the squamocolumnar junction (SCJ) [10,11,12]. Recently, we demonstrated that gastroesophageal reflux disease (GERD) with its endoscopic entities of erosive (ERD) and non-erosive reflux disease (NERD), but not H. pylori infection, leads to distinct lectin-binding patterns at the SCJ [13].…”
Section: Introductionmentioning
confidence: 99%